The influence of information and communication technology in the science of Qira'at - Zulkifli, Zati Syahmeena; Fatah Yasin, Raudlotul Firdaus; Sakib, Nazmus (Kolej Universiti Islam Perlis (KUIPs), 2020)
Information and Communication Technology (ICT) was insignificant until post World War Two (WWII), although it has been existence since the introduction of telegraph followed by the telephone where data (telegraphy) and voice transaction were merely restricted to a two-way communication of voice and text activity. Mobile phones, email, internet and other internet flagship such as portal internet services are the current crucial ICT products. ICT's apparent components which being information and communication technology are almost self-explanatory.